Design, Modeling, and Fatigue Life Analysis of a 450 Kg LPG Cylinder - Dahal, Swikrit; Maharjan, Sanjeev (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Liquefied Petroleum Gas (LPG) cylinders play a critical role in industrial energy storage, with increasing demand for large-capacity units such as 450 kg cylinders in commercial applications. However, their structural integrity and fatigue performance under cyclic loading conditions remain less explored. This study aims to design, model, and evaluate the fatigue life of a 450 kg LPG cylinder using a combination of analytical methods and finite element analysis (FEA), in accordance with EN 13445 and ASME standards. The research methodology integrates thin-walled pressure vessel theory for preliminary design with three-dimensional modeling and numerical simulation to assess stress distribution, deformation, and fatigue behavior. Results indicate that while the general cylindrical shell experiences uniform stress within allowable limits, localized stress concentrations occur at nozzle connections, support structures, and welded regions, with a maximum equivalent stress of 573.07 MPa and deformation of approximately 3 mm. Fatigue analysis using the S–N approach and Miner’s rule indicates that the cylinder can safely withstand the expected service cycles, with a damage factor less than unity and a minimum fatigue life of approximately 57,515 cycles. The study concludes that although the overall design is structurally adequate, fatigue performance is governed by stress-concentration zones, necessitating geometric optimization. The findings have practical implications for improving the safety, reliability, and standardization of large-capacity LPG storage systems in industrial applications. This work contributes to the limited research on large LPG cylinders by providing a combined analytical and numerical framework for design validation and fatigue assessment.